Composite negative electrode material and preparation method and application thereof

By covering the lithium-ion conductor layer and metal oxide layer on the surface of the negative electrode material of the lithium-ion battery, the problems of surface side reactions and structural changes of the negative electrode material during the circulation process are solved, and better circulation and storage performance are achieved, and the overall performance of the lithium-ion battery is improved.

CN120149370APending Publication Date: 2025-06-13ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510331197.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

Existing lithium-ion battery negative electrode materials are prone to surface side reactions and structural changes during the circulation process, resulting in poor circulation and storage performance.

Method used

By using a composite negative electrode material, the ionic conductivity and structural stability of the negative electrode material are improved by coating the lithium ion conductor layer and the metal oxide layer. The specific method includes oxidizing the negative electrode material in an atomic layer deposition device, and then alternately passing into an anion source and a cation source to form a lithium ion conductor layer and a metal oxide layer.

Benefits of technology

The rate performance and cycle stability of the negative electrode material are improved, and the side reactions on the surface of the negative electrode material are suppressed, thereby significantly improving the overall performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120149370A_ABST
    Figure CN120149370A_ABST
Patent Text Reader

Abstract

The invention relates to a composite negative electrode material and a preparation method and application thereof, the composite negative electrode material comprises a negative electrode material, and a lithium ion conductor layer and a metal oxide layer which sequentially coat the surface of the negative electrode material, the material of the lithium ion conductor layer is LizAxOy, xgt; 0, ygt; 0, zgt; 0, A is selected from at least one of Mg, Al, Ti, Mn, Zr, Nb, Mo, V or P, the material of the metal oxide layer is BmOn, and mgt; 0, ngt; b is selected from at least one of Al, Ti, Mg, Zn or Zr, and the thickness of the metal oxide layer is smaller than or equal to 3 nm. The composite negative electrode material has excellent cycle performance and storage performance, and the performance of the lithium ion battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and particularly to a composite negative electrode material, a preparation method thereof, and an application thereof. Background Art

[0002] As an important component of lithium-ion batteries, the improvement of the performance of negative electrode materials is crucial for the improvement of the performance of lithium-ion batteries.

[0003] Research shows that the main reasons affecting the cycle performance and storage performance of negative electrode materials include side reactions on the material surface and structural changes during the cycle. Among them, the side reactions on the material surface include the reduction reaction of the electrolyte on the surface of the charged negative electrode material and the corrosion of the surface of the negative electrode material by the decomposition product hydrogen fluoride of the lithium salt, and the structural change during the cycle refers to the particle fragmentation and pulverization caused by the volume change of the negative electrode material during the lithium intercalation / deintercalation process. Summary of the Invention

[0004] Based on this, it is necessary to provide a composite negative electrode material, a preparation method thereof, and an application thereof for the above problems. The composite negative electrode material has excellent cycle performance and storage performance and can effectively improve the performance of lithium-ion batteries.

[0005] A composite negative electrode material, comprising:

[0006] A negative electrode material;

[0007] A lithium-ion conductor layer coated on the surface of the negative electrode material, and the material of the lithium-ion conductor layer is Li z A x O y where x>0, y>0, z>0, and A is selected from at least one of Mg, Al, Ti, Mn, Zr, Nb, Mo, V, or P;

[0008] A metal oxide layer coated on the surface of the lithium-ion conductor layer, and the material of the metal oxide layer is B m O n where m>0, n>0, B is selected from at least one of Al, Ti, Mg, Zn, or Zr, and the thickness of the metal oxide layer is less than or equal to 3 nm.

[0009] In one embodiment, the lithium-ion conductor layer is selected from at least one of lithium aluminate, lithium titanate, lithium manganate, lithium zirconate, lithium niobate, lithium molybdate, lithium vanadate, or lithium phosphate;

[0010] And / or, the metal oxide layer is selected from at least one of aluminum oxide, titanium oxide, magnesium oxide, zinc oxide, or zirconium oxide.

[0011] In one embodiment, the thickness of the lithium-ion conductor layer is 1 nm - 10 nm;

[0012] And / or, the thickness of the metal oxide layer is 1 nm - 3 nm.

[0013] A method for preparing the composite anode material includes the following steps:

[0014] Place the anode material in an atomic layer deposition device;

[0015] Introduce an oxidant into the atomic layer deposition device to oxidize the anode material;

[0016] Alternately introduce a first anion source and a first cation source into the atomic layer deposition device to coat a lithium ion conductor layer on the surface of the anode material;

[0017] Alternately introduce a second anion source and a second cation source into the atomic layer deposition device to coat a metal oxide layer on the surface of the lithium ion conductor layer.

[0018] In one embodiment, the oxidant is selected from at least one of water, oxygen, ozone, or hydrogen peroxide, the temperature of the oxidation treatment is 100°C - 300°C, and the time is 0.5 h - 3 h.

[0019] In one embodiment, the first anion source is selected from at least one of aluminum isopropoxide, titanium tetraisopropoxide, manganese tris(2,2,6,6 - tetramethyl - 3,5 - heptenoate), zirconium tetrabutoxide, niobium ethoxide, pentaethoxymolybdenum, pentaethoxyvanadium, or trimethyl phosphate, and the first cation source is selected from at least one of lithium tert - butoxide, trimethyllithium, butyllithium, or phenyllithium.

[0020] In one embodiment, the second anion source is selected from at least one of water, oxygen, ozone, or hydrogen peroxide, and the second cation source is selected from at least one of trimethylaluminum, titanium tetrachloride, magnesium chloride, trimethylmagnesium, zinc chloride, or zirconium chloride.

[0021] An anode sheet, the anode sheet includes the composite anode material described above.

[0022] A lithium ion battery, the lithium ion battery includes the anode sheet described above.

[0023] A vehicle, the vehicle uses the lithium ion battery described above.

[0024] The present invention adopts a coating method, by selecting oxygen - containing Li z A x O yThe material is first coated to form a lithium ion conductor layer, and then a specific metal oxide is selected for coating to form a metal oxide layer and the thickness of the metal oxide layer is controlled. On the one hand, the ionic conductivity of the negative electrode material can be improved, the lithium ion transmission can be accelerated, and thus the rate performance of the negative electrode material can be improved. On the other hand, the structural stability of the negative electrode material can be maintained, and the side reactions on the surface of the negative electrode material can be inhibited. Therefore, the composite negative electrode material of the present invention has excellent cycle performance and storage performance, and can effectively improve the performance of lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application or in the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.

[0026] Figure 1 It is a schematic structural diagram of the composite negative electrode material of the present invention.

[0027] In the figure: 10, negative electrode material; 20, lithium ion conductor layer; 30, metal oxide layer. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0028] To facilitate the understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure content of the present invention more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which the present invention belongs. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments or examples, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of the related listed items. The any and all combinations include any two related listed items, any more related listed items, or all related listed items.

[0030] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when the range refers to integers, it includes each integer between the minimum and maximum values of the range. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein.

[0031] As Figure 1 shown, the composite anode material provided by the present invention includes an anode material 10, and a lithium ion conductor layer 20 and a metal oxide layer 30 sequentially coated on the surface of the anode material 10. Among them, the anode material 10 is selected from common anode materials such as graphite materials and silicon-based materials, and the present invention places no restrictions thereon.

[0032] Specifically, the material of the lithium ion conductor layer 20 coated on the surface of the anode material 10 is Li z A x O y , where x > 0, y > 0, z > 0, and A is selected from at least one of Mg, Al, Ti, Mn, Zr, Nb, Mo, V, or P. The material of the metal oxide layer 30 coated on the surface of the lithium ion conductor layer 20 is B m O n , where m > 0, n > 0, B is selected from at least one of Al, Ti, Mg, Zn, or Zr, and the thickness of the metal oxide layer 30 is less than or equal to 3 nm.

[0033] Thus, by first selecting an oxygen-containing Li z A x O y material to coat and form the lithium ion conductor layer 20, and then selecting a specific metal oxide to coat and form the metal oxide layer 30 and controlling the thickness of the metal oxide layer 30, on the one hand, it can improve the ionic conductivity of the anode material 10, accelerate the lithium ion transmission, and thus improve the rate performance of the anode material 10. On the other hand, it can maintain the structural stability of the anode material 10 and inhibit the side reactions on the surface of the anode material 10. Therefore, the composite anode material of the present invention has excellent cycle performance and storage performance, and can effectively improve the performance of lithium ion batteries.

[0034] According to Li z A x O yThe selection of A in the material and the values of x, y, and z can result in different lithium-ion conductor materials. Optionally, the lithium-ion conductor layer 20 is preferably selected from at least one of lithium aluminate, lithium titanate, lithium manganate, lithium zirconate, lithium niobate, lithium molybdate, lithium vanadate, or lithium phosphate. The thickness of the lithium-ion conductor layer 20 is preferably 1 nm - 10 nm, such as 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc., or the range formed by any two of these values.

[0035] According to B m O n The selection of B in the material and the values of m and n can result in different metal oxide materials. Optionally, the metal oxide layer 30 is preferably selected from at least one of aluminum oxide, titanium oxide, magnesium oxide, zinc oxide, or zirconium oxide. The thickness of the metal oxide layer 30 is preferably 1 nm - 3 nm, such as 1 nm, 2 nm, 3 nm, etc., or the range formed by any two of these values.

[0036] In the present invention, the lithium-ion conductor layer 20 and the metal oxide layer 30 can be coated in the same or different ways, and the coating method is not limited. Among them, atomic layer deposition (ALD) deposits at the atomic level by alternately introducing precursor gases, and has the advantages of low operating temperature, coating integrity, uniformity, and consistency. Therefore, the present invention also provides a method for preparing the composite negative electrode material, including the following steps:

[0037] S1, placing the negative electrode material 10 in an atomic layer deposition device;

[0038] S2, introducing an oxidant into the atomic layer deposition device to oxidize the negative electrode material 10;

[0039] S3, alternately introducing a first anion source and a first cation source into the atomic layer deposition device to coat the lithium-ion conductor layer 20 on the surface of the negative electrode material 10;

[0040] S4, alternately introducing a second anion source and a second cation source into the atomic layer deposition device to coat the metal oxide layer 30 on the surface of the lithium-ion conductor layer 20.

[0041] In step S2, oxidizing the negative electrode material 10 with an oxidant can form more oxygen-containing functional groups on the surface of the negative electrode material 10, so as to be able to form a more complete and denser coating layer on the surface of the negative electrode material 10.

[0042] Optionally, the oxidizing agent is selected from at least one of water, oxygen, ozone or hydrogen peroxide. The temperature of the oxidation treatment is preferably 100°C - 300°C, such as 100°C, 150°C, 200°C, 250°C, 300°C, etc. The time is preferably 0.5h - 3h, such as 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, etc., or the range composed of any two of these values.

[0043] In step S3, when coating the lithium ion conductor layer 20, the alternately introduced precursor gases include a first anion source and a first cation source. Among them, the first anion source is selected from at least one of aluminum isopropoxide, titanium tetraisopropoxide, manganese tris(2,2,6,6-tetramethyl-3,5-heptenoate), tetrabutyl zirconate, niobium ethoxide, pentaethoxymolybdenum, pentaethoxyvanadium or trimethyl phosphate, and the first cation source is selected from at least one of lithium tert-butoxide, trimethyllithium, butyllithium or phenyllithium.

[0044] In step S4, when coating the metal oxide layer 30, the alternately introduced precursor gases include a second anion source and a second cation source. Among them, the second anion source is selected from at least one of water, oxygen, ozone or hydrogen peroxide, and the second cation source is selected from at least one of trimethylaluminum, titanium tetrachloride, magnesium chloride, trimethylmagnesium, zinc chloride or zirconium chloride.

[0045] It can be understood that the process of atomic layer deposition includes four steps: adsorption, reaction, purification and repetition. In steps S2 and S3 of the present invention, the first anion source and the second anion source are respectively introduced to saturate and adsorb on the surface of the material to be coated, and then the first cation source and the second cation source are respectively introduced to react with the first anion source and the second anion source to form a single-layer atomic film, and then an inert gas such as nitrogen is used for flushing to remove the unreacted precursor gases and by-products, and then the above steps are repeated to deposit layer by layer until the required thickness is reached.

[0046] The present invention also provides a negative electrode sheet including the composite negative electrode material described above. It can be understood that the negative electrode sheet includes a current collector and a negative electrode active material layer attached to the surface of the current collector, and the negative electrode active material layer is made of the composite negative electrode material, binder, conductive agent, etc. in proportion.

[0047] Furthermore, the present invention also provides a lithium ion battery including the negative electrode sheet described above. The lithium ion battery using this negative electrode sheet has excellent rate performance and cycle stability.

[0048] Furthermore, the present invention also provides a vehicle using the lithium ion battery described above. The vehicle using this lithium ion battery has a longer endurance and higher safety performance.

[0049] Hereinafter, the composite anode material, its preparation method and application will be further described by the following specific examples.

[0050] Example 1

[0051] Put the graphite material into the atomic layer deposition equipment, evacuate and replace nitrogen three times repeatedly. Subsequently, water vapor is introduced into the atomic layer deposition equipment, and oxidation treatment is carried out at 100 °C for 3 h, and then evacuate and replace nitrogen three times repeatedly.

[0052] Heat up to 200 °C, eject trimethyl phosphate gas in pulses, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it away for 60 s to remove the excess trimethyl phosphate; eject lithium tert-butoxide gas in pulses, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it away for 60 s to remove the excess lithium tert-butoxide; cycle 50 times to form a Li 3 PO 4 layer with a thickness of 5 nm on the surface of the graphite material.

[0053] Eject water vapor in pulses, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it away for 60 s to remove the excess water vapor; eject trimethylaluminum gas in pulses, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it away for 60 s to remove the excess trimethylaluminum; cycle 10 times to form an Al 3 PO 4 layer on the surface of the Li 2 O 3 layer with a thickness of 1 nm.

[0054] Example 2

[0055] Put the graphite material into the atomic layer deposition equipment, evacuate and replace nitrogen three times repeatedly. Subsequently, ozone is introduced into the atomic layer deposition equipment, and oxidation treatment is carried out at 300 °C for 0.5 h, and then evacuate and replace nitrogen three times repeatedly.

[0056] Heat up to 150 °C, eject pentaethoxyvanadium gas in pulses, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it away for 60 s to remove the excess pentaethoxyvanadium; eject lithium tert-butoxide gas in pulses, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it away for 60 s to remove the excess lithium tert-butoxide; cycle 10 times to form a LiVO 3 layer with a thickness of 1 nm on the surface of the graphite material.

[0057] The water vapor is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive water vapor; trimethylmagnesium gas is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive trimethylmagnesium; the cycle is repeated 20 times, and a MgO layer with a thickness of 2 nm is coated on the surface of the LiVO 3 layer.

[0058] Example 3

[0059] The graphite material is placed in the atomic layer deposition equipment, and the vacuum is repeatedly evacuated and nitrogen is replaced three times. Subsequently, ozone is introduced into the atomic layer deposition equipment, and oxidation treatment is carried out at 300 °C for 0.5 h, and then the vacuum is repeatedly evacuated and nitrogen is replaced three times.

[0060] The temperature is raised to 150 °C, niobium ethoxide gas is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive niobium ethoxide; trimethyllithium gas is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive trimethyllithium; the cycle is repeated 10 times, and a LiNbO 3 layer with a thickness of 1 nm is coated on the surface of the graphite material.

[0061] Ozone is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive ozone; zinc chloride vapor is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive zinc chloride; the cycle is repeated 20 times, and a ZnO 3 layer is coated on the surface of the LiNbO 2 layer with a thickness of 2 nm.

[0062] Example 4

[0063] The silicon-carbon material is placed in the atomic layer deposition equipment, and the vacuum is repeatedly evacuated and nitrogen is replaced three times. Subsequently, ozone is introduced into the atomic layer deposition equipment, and oxidation treatment is carried out at 200 °C for 0.5 h, and then the vacuum is repeatedly evacuated and nitrogen is replaced three times.

[0064] The temperature is raised to 150 °C, pentaethoxymolybdenum gas is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive pentaethoxymolybdenum; trimethyllithium gas is ejected in the form of pulses, carried by nitrogen into the atomic layer deposition equipment, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove the excessive trimethyllithium; the cycle is repeated 100 times, and a Li 2 MoO4 layer with a thickness of 10 nm.

[0065] Ozone is ejected in the form of pulses, introduced into the atomic layer deposition equipment with nitrogen as the carrier, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove excess water vapor; titanium tetrachloride vapor is ejected in the form of pulses, introduced into the atomic layer deposition equipment with nitrogen as the carrier, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove excess titanium tetrachloride; this is cycled 20 times, and on the surface of the Li 2 MoO 4 layer, a TiO 2 layer is coated, with a thickness of 2 nm.

[0066] Example 5

[0067] The silicon-carbon material is placed in the atomic layer deposition equipment, and vacuum is pumped and nitrogen is replaced three times repeatedly. Subsequently, ozone is introduced into the atomic layer deposition equipment and subjected to oxidation treatment at 200 °C for 0.5 h, and then vacuum is pumped and nitrogen is replaced three times repeatedly.

[0068] The temperature is raised to 150 °C, aluminum isopropoxide gas is ejected in the form of pulses, introduced into the atomic layer deposition equipment with nitrogen as the carrier, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove excess aluminum isopropoxide; butyllithium gas is ejected in the form of pulses, introduced into the atomic layer deposition equipment with nitrogen as the carrier, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove excess butyllithium; this is cycled 100 times, and on the surface of the graphite material, a LiAlO 2 layer is coated, with a thickness of 10 nm.

[0069] Ozone is ejected in the form of pulses, introduced into the atomic layer deposition equipment with nitrogen as the carrier, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove excess water vapor; trimethylmagnesium is ejected in the form of pulses, introduced into the atomic layer deposition equipment with nitrogen as the carrier, then left standing for 5 s, and nitrogen is introduced to blow it away for 60 s to remove excess trimethylmagnesium; this is cycled 20 times, and on the surface of the LiAlO 2 layer, a MgO layer is coated, with a thickness of 2 nm.

[0070] Example 6

[0071] The silicon-carbon material is placed in the atomic layer deposition equipment, and vacuum is pumped and nitrogen is replaced three times repeatedly. Subsequently, ozone is introduced into the atomic layer deposition equipment and subjected to oxidation treatment at 200 °C for 0.5 h, and then vacuum is pumped and nitrogen is replaced three times repeatedly.

[0072] Heat up to 150 °C, eject molybdenum pentaethoxide gas in pulse form, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it for 60 s to remove excessive molybdenum pentaethoxide; eject trimethyl lithium gas in pulse form, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it for 60 s to remove excessive trimethyl lithium; cycle 100 times to form a Li 2 MoO 4 layer with a thickness of 10 nm.

[0073] Eject ozone in pulse form, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it for 60 s to remove excessive water vapor; eject zirconium chloride vapor in pulse form, introduce it into the atomic layer deposition equipment with nitrogen as the carrier, then stand still for 5 s, and introduce nitrogen to blow it for 60 s to remove excessive zirconium chloride; cycle 20 times to form a ZrO 2 MoO 4 layer on the surface of the Li 2 layer with a thickness of 2 nm.

[0074] Comparative Example 1

[0075] The difference between Comparative Example 1 and Example 1 is only that only the Li 3 PO 4 layer is coated, and there is no Al 2 O 3 layer.

[0076] Comparative Example 2

[0077] The difference between Comparative Example 2 and Example 1 is only that only the Al 2 O 3 layer is coated, and there is no Li 3 PO 4 layer.

[0078] Comparative Example 3

[0079] The difference between Comparative Example 3 and Example 1 is only that the atomic layer deposition of Li 3 PO 4 layer is replaced with the atomic layer deposition of LiF layer with a thickness still of 5 nm.

[0080] Comparative Example 4

[0081] The difference between Comparative Example 4 and Example 1 is only that the atomic layer deposition of Li 3 PO 4 layer is replaced with the atomic layer deposition of Li 3 N layer with a thickness still of 5 nm.

[0082] Comparative Example 5

[0083] The difference between Comparative Example 5 and Example 1 is only that the atomic layer deposition Al 2 O 3 layer is replaced with an atomic layer deposition Fe 2 O 3 layer with a thickness of 1 nm.

[0084] Comparative Example 6

[0085] The difference between Comparative Example 6 and Example 1 is only that the atomic layer deposition Al 2 O 3 layer is replaced with an atomic layer deposition MoO 3 layer with a thickness of 1 nm.

[0086] Comparative Example 7

[0087] The difference between Comparative Example 7 and Example 1 is only that the atomic layer deposition Al 2 O 3 layer is replaced with an atomic layer deposition NiO layer with a thickness of 1 nm.

[0088] Comparative Example 8

[0089] The difference between Comparative Example 8 and Example 1 is only that the thickness of the Al 2 O 3 layer is increased to 5 nm.

[0090] The composite anode materials prepared using Examples 1 - 6 and Comparative Examples 1 - 8 were used to prepare anode sheets, and then the anode sheets were assembled into lithium-ion coin half-cells. The process is as follows:

[0091] Using deionized water as a solvent, the composite anode material, Super P, CMC, and SBR were prepared into an anode slurry according to a mass ratio of 95:2:1.5:1.5. The slurry was scraped into a single side with a spatula and then punched into an anode sheet with a diameter of 16 mm. The anode sheet wetted with the electrolyte, the separator, the lithium sheet, the gasket, and the spring sheet were successively placed in the middle of the positive end of the stainless-steel battery case, strictly aligned, and then an appropriate amount of electrolyte was dropped. The negative battery case was covered and pressed tightly with forceps, and then sealed and formed with a sealer. The entire assembly process was carried out in a sealed glove box filled with high-purity argon (O 2 <0.1 ppm, H 2 O <0.1 ppm). In the experiment, metallic lithium was used as the counter electrode, a 1 mol / L LiPF 6 EC / DEC (volume ratio 1:1) mixed solution was used as the electrolyte, and a Celgard-2400 polypropylene PP film was used as the separator. The assembled coin cells were left for 12 h to allow the electrode materials to be fully wetted by the electrolyte before subsequent battery performance tests. The results are shown in Tables 1 and 2, and the relevant test conditions are as follows:

[0092] Initial discharge specific capacity, initial charge specific capacity, and initial Coulombic efficiency: At 25 ± 2°C, discharge at a constant current of 0.1C with constant voltage (constant voltage until the current rate is less than or equal to 0.01C and then cut off) to 0.005V, and record the initial discharge specific capacity as D1; subsequently, charge at a constant current of 0.1C to 2.0V, record the initial charge specific capacity as C1, and record the initial Coulombic efficiency as C1 / D1;

[0093] Room temperature 0.33C cycling: At 25 ± 2°C, discharge at a constant current of 0.33C with constant voltage to 0.005V (constant voltage until the current rate is less than or equal to 0.01C and then cut off), charge at a constant current of 0.33C to 2.0V, record the charge capacity as C1, after cycling a certain number of turns, record the charge capacity as C2, and the room temperature cycling performance is characterized as C2 / C1 (%);

[0094] Rate discharge: At 25 ± 2°C, after the first cycle at 0.1C, discharge at a constant current of 0.1C to 0.005V, record the discharge specific capacity as D1; subsequently, charge at a constant current of 0.1C to 2.0V, and discharge at a constant current of 1C to 0.005V, record the discharge specific capacity as D2, and the rate discharge performance is characterized as D2 / D1.

[0095] Table 1

[0096]

[0097] Table 2

[0098]

[0099] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as the scope described in this specification.

[0100] The above-described embodiments only represent several implementation manners of the present invention. Their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent should be subject to the appended claims.

Claims

1. A composite negative electrode material, characterized in that: include: Anode material; The lithium ion conductor layer coated on the surface of the negative electrode material, the material of the lithium ion conductor layer is Li z A x O y , wherein x>0, y>0, z>0, A is selected from at least one of Mg, Al, Ti, Mn, Zr, Nb, Mo, V or P; The metal oxide layer coated on the surface of the lithium ion conductor layer is made of B m O n , wherein m>0, n>0, B is selected from at least one of Al, Ti, Mg, Zn or Zr, and the thickness of the metal oxide layer is less than or equal to 3 nm.

2. The composite negative electrode material according to claim 1, characterized in that: The lithium ion conductor layer is selected from at least one of lithium aluminate, lithium titanate, lithium manganate, lithium zirconate, lithium niobate, lithium molybdate, lithium vanadate or lithium phosphate; And / or, the metal oxide layer is selected from at least one of aluminum oxide, titanium oxide, magnesium oxide, zinc oxide or zirconium oxide.

3. The composite negative electrode material according to claim 1, characterized in that: The thickness of the lithium ion conductor layer is 1nm-10nm; And / or, the thickness of the metal oxide layer is 1 nm-3 nm.

4. A method for preparing a composite negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: placing the negative electrode material in an atomic layer deposition device; Introducing an oxidant into an atomic layer deposition device to oxidize the negative electrode material; Alternately introducing a first anion source and a first cation source into an atomic layer deposition device to coat a lithium ion conductor layer on the surface of the negative electrode material; A second anion source and a second cation source are alternately introduced into the atomic layer deposition device to coat the surface of the lithium ion conductor layer with a metal oxide layer.

5. The method for preparing a composite negative electrode material according to claim 4, characterized in that: The oxidant is selected from at least one of water, oxygen, ozone or hydrogen peroxide, and the oxidation treatment temperature is 100° C.-300° C., and the time is 0.5 h-3 h.

6. The method for preparing a composite negative electrode material according to claim 4, characterized in that: The first anion source is selected from at least one of aluminum isopropoxide, titanium tetraisopropoxide, tri(2,2,6,6-tetramethyl-3,5-heptenoate)manganese, tetrabutyl zirconate, niobium ethoxide, pentaethoxy molybdenum, pentaethoxy vanadium or trimethyl phosphate, and the first cation source is selected from at least one of lithium tert-butoxide, trimethyl lithium, butyl lithium or phenyl lithium.

7. The method for preparing a composite negative electrode material according to claim 4, characterized in that: The second anion source is selected from at least one of water, oxygen, ozone or hydrogen peroxide, and the second cation source is selected from at least one of trimethylaluminum, titanium tetrachloride, magnesium chloride, trimethylmagnesium, zinc chloride or zirconium chloride.

8. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the composite negative electrode material according to any one of claims 1 to 3.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 8.

10. A vehicle, characterized in that: The vehicle uses the lithium-ion battery as claimed in claim 9.

Citation Information

Cited By

  • Graphite negative electrode material, preparation method thereof and lithium battery

    CN122474611A

  • Graphite negative electrode material, preparation method thereof and lithium battery

    CN122474611B